Electrode, anode for water electrolysis, electrolysis cell, and method for producing hydrogen

JP7629776B2Active Publication Date: 2025-02-14ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021052313
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-25
Publication Date
2025-02-14
Estimated Expiration
2041-03-25

AI Technical Summary

Benefits of technology

【0012】 本発明によれば、低い酸素過電圧を有し、かつ高温のアルカリへの耐久性に優れた安価な電極、水電解用陽極及びこの水電解用陽極を備えた水電解セルを得られる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007629776000004
    Figure 0007629776000004
  • Figure 0007629776000005
    Figure 0007629776000005
  • Figure 0007629776000006
    Figure 0007629776000006
Patent Text Reader

Abstract

To provide: an electrode having a low overvoltage of oxygen evolution and high temperature alkali resistance; an anode for water electrolysis; a bipolar electrolytic cell using the anode for water electrolysis; and a hydrogen production method using the anode for water electrolysis.SOLUTION: There is provided an electrode having LaNixMyO3-z(x+y is 0.8 or more and 1.2 or less, y is 0.001 or more and 0.6 or less, z is -0.5 or more and 0.5 or less, M includes at least one of Nb, Ta, Sb, Ti, Mn and Zr) on a substrate, wherein the XRD main peak position (2θ) of LaNixMyO3-z is 32.6° or more and 33.2° or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode, an anode for water electrolysis, a bipolar electrolytic cell using the anode for water electrolysis, and a method for producing hydrogen using the anode for water electrolysis. [Background technology]

[0002] In recent years, hydrogen produced using renewable energy has been attracting attention as a clean energy source that can solve problems such as global warming caused by CO2 and dwindling fossil fuel reserves. Hydrogen production using renewable energy requires low costs comparable to those of conventional hydrogen production by reforming fossil fuels. Therefore, hydrogen production using renewable energy requires high levels of energy efficiency and inexpensive equipment that could not be achieved with conventional technologies.

[0003] One method for producing hydrogen that can meet the above requirements is electrolytic decomposition of water (water electrolysis). For example, several ideas have been proposed for producing hydrogen by water electrolysis using power generation from natural energies such as wind power or solar power, and storing or transporting the hydrogen.

[0004] In water electrolysis, oxygen is generated at the anode and hydrogen is generated at the cathode by passing an electric current through the water. The main cause of energy loss in electrolysis is the overvoltage of the anode and cathode. Reducing this overvoltage makes it possible to produce hydrogen efficiently. In particular, the overvoltage of the anode is higher than that of the cathode, and research and development into reducing the overvoltage of the anode is being widely conducted.

[0005] Among oxides having a perovskite structure, materials with high oxygen generating capacity are known, and they have attracted attention as anode materials for water electrolysis (Non-Patent Document 1). In order to use an oxide having a perovskite structure as an anode for alkaline water electrolysis, there is a method of forming an oxide layer on the surface of a conductive substrate. For example, Patent Document 1 discloses an anode for water electrolysis that has low oxygen overvoltage and high durability by forming a metal oxide layer having a high content of perovskite oxide in the crystalline component on the surface of a nickel porous substrate, and a water electrolysis device using the anode. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2018 / 155503 [Non-patent literature]

[0007] [Non-Patent Document 1] Science, 2011, 334, 1383 Summary of the Invention [Problem to be solved by the invention]

[0008] The anode described in Patent Document 1 exhibits high durability against long-term application of current, but it has been found to have a problem in that overvoltage increases when the anode is immersed in an alkaline electrolyte at a particularly high liquid temperature in a non-current-carrying state.

[0009] The present invention has been made in consideration of the above problems, and an object of the present invention is to provide an electrode having a low overvoltage for oxygen evolution and high high-temperature alkaline durability, an anode for water electrolysis, a bipolar electrolytic cell using the anode for water electrolysis, and a method for producing hydrogen using the anode for water electrolysis. [Means for solving the problem]

[0010] The present inventors have conducted extensive research and experiments to solve the above problems. As a result, they have developed a LaNi alloy having a specific composition and structure on a substrate. x M y O 3-z The inventors have found that an electrode having a layer formed thereon has a low oxygen overvoltage and high durability at high temperatures and in alkaline conditions and can be used as an anode for water electrolysis, thereby completing the present invention.

[0011] That is, the present invention is as follows. [1] LaNi x M y O 3-z (x+y is 0.8 or more and 1.2 or less, y is 0.001 or more and 0.6 or less, z is -0.5 or more and 0.5 or less, and M contains at least one of Nb, Ta, Sb, Ti, Mn, and Zr), and LaNi x M y O 3-z The electrode is characterized in that the XRD main peak position 2θ is 32.6° or more and 33.2° or less. [2] The electrode according to [1], wherein y is 0.002 or more and less than 0.2. [3] LaNi x M y O 3-z The electrode according to [1] or [2], wherein the XRD main peak position 2θ is 32.7° or more and 33.2° or less. [4] The electrode according to any one of [1] to [3], wherein M is Nb. [5] LaNi x M y O 3-z The electrode according to any one of [1] to [4], wherein the XRD main peak half width is 0.6° or more and 0.85° or less. [6]LaNi x M y O 3-z The electrode according to any one of [1] to [5], wherein the XRD main peak intensity is 6,000 or more and 100,000 or less. [7] An electrolytic cell comprising the electrode according to any one of [1] to [6] as an anode. [8] A method for producing hydrogen by electrolyzing alkali-containing water in an electrolytic cell, the electrolytic cell having at least an anode and a cathode, the anode having a LaNi x M y O 3-z (x+y is 0.8 or more and 1.2 or less, y is 0.001 or more and 0.6 or less, z is -0.5 or more and 0.5 or less, and M contains at least one of Nb, Ta, Sb, Ti, Mn, and Zr), and LaNi x M y O 3-z The method for producing hydrogen is characterized in that the XRD main peak position 2θ is 32.6° or more and 33.2° or less. Effect of the Invention

[0012] According to the present invention, it is possible to obtain an inexpensive electrode having a low oxygen overvoltage and excellent durability against high-temperature alkali, an anode for water electrolysis, and a water electrolysis cell including the anode for water electrolysis. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a side view showing an example of an entire electrolytic cell including an electrolytic cell having the electrode of the present embodiment as an anode. [Diagram 2] 2 is a diagram showing a cross section of the inside of an electrolytic cell of an electrolytic cell including an electrode of the present embodiment as an anode, the electrolytic cell being a part enclosed in a dashed rectangular frame in FIG. 1. FIG. [Diagram 3] FIG. 1 is a diagram showing an outline of an electrolysis device used in Examples and Comparative Examples. [Figure 4] FIG. 1 is a diagram showing an outline of a bipolar electrolytic cell used in an electrolysis test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, an embodiment for carrying out the present invention (hereinafter, referred to as "the present embodiment") will be described in detail. Note that the following present embodiment is an example for explaining the present invention, and is not intended to limit the present invention. Furthermore, the present invention can be modified in various ways without departing from the gist of the present invention.

[0015] (electrode) In this embodiment, the electrode has at least a substrate. The substrate is preferably conductive. Examples of the material of the conductive substrate include nickel, materials mainly composed of nickel, titanium, GC (glassy carbon), tantalum, zirconium, gold, platinum, palladium, etc. Examples of materials mainly composed of nickel include nickel-based alloys such as Monel, Inconel, and Hastelloy. From the viewpoint of heat resistance in the firing step during electrode preparation, the material of the substrate is preferably a metal, and further preferably nickel or a material mainly composed of nickel, which is a metal that is not dissolved even at the oxygen generating potential in an alkaline aqueous solution and is available at a lower cost than precious metals, from the viewpoints of durability, electrical conductivity, and economy. The shape of the conductive substrate of the electrode may be a flat plate, or a porous body having a large number of holes. Specific shapes of the porous body include expanded metal, punched metal, plain weave mesh, foam metal, or shapes similar thereto. Among these, expanded metal is preferred, and the dimensions are not particularly limited. However, in order to achieve both an increase in the amount of gas generated due to an increase in the electrolysis surface area and efficient removal of the gas generated by electrolysis from the electrode surface, and from the viewpoint of mechanical strength, it is preferable that the center-to-center distance (SW) in the short direction of the mesh is 2 mm or more and 5 mm or less, the center-to-center distance (LW) in the long direction of the mesh is 3 mm or more and 10 mm or less, the thickness is 0.2 mm or more and 2 mm or less, and the opening ratio is 20% or more and 80% or less. More preferably, SW is 3 mm or more and 4 mm or less, LW is 4 mm or more and 6 mm or less, the thickness is 0.8 mm or more and 1.5 mm or less, and the opening ratio is 40% or more and 60% or less.

[0016] In this embodiment, LaNi x M y O 3-z (x+y is 0.8 or more and 1.2 or less, y is 0.001 or more and 0.6 or less, z is -0.5 or more and 0.5 or less, and M includes at least one of Nb, Ta, Sb, Ti, Mn, and Zr). In this embodiment, as a metal oxide having a perovskite structure, high oxygen generating ability can be realized by disposing Ni at least in a part of the B site. Furthermore, disposing element M at the B site together with Ni is one of the requirements for imparting durability to high-temperature alkali. The element M includes at least one of Nb, Ta, Sb, Ti, Mn, and Zr. M may include two or more of Nb, Ta, Sb, Ti, Mn, and Zr. As M, from the viewpoint of being able to impart durability to high-temperature alkali with a small amount of addition, Nb, Ta, Sb, Ti, and Zr are preferred, from the viewpoint of excellent durability to high-temperature alkali, Ta, Sb, and Ti are more preferred, and from the viewpoint of being able to achieve both durability to high-temperature alkali and overvoltage with a small amount of addition, Nb is the most preferred. From the viewpoint of high-temperature alkali resistance, x+y is 0.8 or more and 1.2 or less. From the viewpoint of achieving both high-temperature alkali resistance and overvoltage, x+y is preferably 0.8 or more and 1.05 or less, and more preferably 1.0 or more and 1.05 or less. From the viewpoint of high-temperature alkali resistance, y is 0.001 or more and 0.6 or less. From the viewpoint of achieving both high-temperature alkali resistance and overvoltage, y is preferably 0.002 or more and less than 0.2, and more preferably 0.005 or more and 0.1 or less. z is -0.5 or more and 0.5 or less. In the present invention, z is determined by the composition ratio 3-z of O calculated so that the valence balance of the composition formula is balanced, with La being trivalent, Ni being trivalent, Nb being pentavalent, Ta being pentavalent, Sb being pentavalent, Ti being tetravalent, Mn being trivalent, Zr being tetravalent, and O being -2. For example, in the composition formula LaNi x Zr y O 3-z If x = 0.9 and y = 0.1, then the relationship 3-z = (3+3×0.9+4×0.1) / 2 gives us z = -0.05. On the substrate, LaNi x M y O 3-z(x+y is 0.8 or more and 1.2 or less, y is 0.001 or more and 0.6 or less, z is −0.5 or more and 0.5 or less, and M includes at least one of Nb, Ta, Sb, Ti, Mn, and Zr) can be confirmed by a known method such as a method of peeling off the metal oxide layer on the substrate, dissolving it in an acid such as aqua regia, and performing a composition analysis by ICP-AES (inductively coupled plasma atomic emission spectroscopy), a method of peeling off the metal oxide layer on the substrate and performing a composition analysis by an X-ray fluorescence analyzer, or SEM-EDX analysis of the cross section of the electrode.

[0017] In this embodiment, LaNi x M y O 3-z The third characteristic is that the XRD main peak position 2θ is 32.6° or more and 33.2° or less. In this embodiment, LaNi x M y O 3-z The XRD main peak position of the electrode shifts depending on the electrode. However, when the XRD (X-ray diffraction) of the electrode was measured using Cu Kα1 radiation as the X-ray source, the peak near 2θ=32.5°~33.2° was determined to be LaNiO3 (104) plane main peak position 2θ=33.166° on the PDF01-070-5757 card. x M y O 3-z The main peak position is defined as LaNi x M y O 3-z The main peak position of is calculated after shifting and correcting the XRD spectrum using the "X-axis offset" tool so that the NiO main peak position 2θ near 2θ = 43.276° corresponds to 2θ = 43.276° of the NiO (200) plane in the PDF00-047-1049 card data. LaNi x M y O 3-z The XRD main peak position 2θ is 32.6° or more and 33.2° or less from the viewpoint of high temperature alkali resistance.

[0018] The present inventors have produced LaNiO3 by substituting a predetermined amount of Ni with element M or adding a predetermined amount of element M to LaNiO3. x M y O 3-z The XRD main peak position 2θ was controlled to be 32.6° to 33.2°. x M y O 3-z However, they found that LaNi has a surprisingly high resistance to high-temperature alkali. x M y O 3-z By setting the XRD main peak position 2θ to 32.6° or more and 33.2°, the high temperature alkali and LaNi x M y O 3-z The concentration of oxygen vacancies, which are the reaction sites of LaNi, is reduced, and the addition of element M improves the thermal stability of LaNi in high-temperature alkali. x M y O 3-z This is believed to be because the generation of oxygen defects in the silicon substrate was suppressed.

[0019] From the viewpoint of excellent durability to high-temperature alkali, the angle is preferably 32.7° or more and 33.2° or less, and from the viewpoint of achieving both durability to high-temperature alkali and overvoltage, the angle is more preferably 32.75° or more and 33.2° or less, and most preferably 32.8° or more and 33.2° or less.

[0020] In this embodiment, LaNi x M y O 3-z From the viewpoint of durability against high-temperature alkali, the XRD main peak half width is preferably 0.6° or more and 0.85° or less. The main peak half width refers to the half width calculated with the peak in the 2θ range of 31° or more and 35° or less. LaNi x M y O 3-z The XRD main peak half width is more preferably 0.6° or more and 0.8° or less, and from the viewpoint of achieving both high-temperature alkali durability and overvoltage, is further preferably 0.6° or more and 0.75° or less.

[0021] In this embodiment, LaNi x M y O 3-z From the viewpoint of durability against high-temperature alkali, the XRD main peak intensity is preferably 6,000 or more and 100,000 or less. The main peak intensity refers to the intensity obtained by subtracting the baseline intensity from the measured intensity (Counts) at the peak position of the main peak measured using an XRD measurement device D8 ADVANCE (sold by Bruker Japan Co., Ltd.). The measurement conditions will be described later in the examples. LaNi x M y O 3-z The XRD main peak intensity is more preferably 6,500 or more and 5,0000 or less, further preferably 7,000 or more and 20,000 or less, and from the viewpoint of achieving both high-temperature alkali durability and overvoltage, it is most preferably 7,000 or more and 17,000 or less.

[0022] The electrode of the present embodiment can be put to practical use as an anode for water electrolysis, and it is possible to provide an electrolytic cell for water electrolysis using the electrode of the present embodiment as an anode, and a method for producing hydrogen using the anode for water electrolysis. Water containing an alkali may be used for water electrolysis.

[0023] (Electrode Preparation Method) The electrode of this embodiment is prepared by applying an aqueous solution (coating liquid) containing metal salts of La, Ni, and M to a substrate, drying and pre-firing the substrate, and depositing a predetermined weight of LaNi x M y O 3-z The precursor can be prepared by forming the precursor and then subjecting it to main calcination.

[0024] The metal salt may be a water-soluble salt such as a nitrate, oxynitrate, chloride, oxalate, tartrate, acetate, sulfate, etc. The metal salt may be either anhydrous or hydrated. For La, Ni, and M, a water-dispersible sol of an oxide or hydroxide may be used instead of a metal salt. When Nb is used as M, it is preferable to use niobium oxalate or ammonium niobium oxalate from the viewpoint of solubility. When Sb is used as M, it is preferable to use antimony tartrate. Adding organic ligands such as amino acids such as glycine, and carboxylic acids such as oxalic acid and tartaric acid to the coating solution makes the LaNi alloy highly resistant to high-temperature alkali. x M y O 3-z This is preferable from the viewpoint of facilitating the preparation of the above-mentioned compound. In particular, when a coating solution in which glycine and a metal nitrate are dissolved is used, it becomes easy to prepare an electrode that has both high durability against high-temperature alkali and an overvoltage, and therefore glycine is a preferred organic ligand.

[0025] The concentration of an aqueous solution containing metal salts of La, Ni, and M is LaNi x M y O 3-z The standard molar concentration is preferably 0.1 mol / kg or more and 4 mol / kg or less. At 0.1 mol / kg or more, electrodes can be prepared with fewer coatings. At 4 mol / kg or less, metal salts and organic ligands are easily dissolved, which is preferable from the viewpoint of productivity of the coating solution. More preferably, it is 0.2 mol / kg or more and 2.0 mol / kg or less, and even more preferably, it is 0.2 mol / kg or more and 1.0 mol / kg or less.

[0026] After the coating liquid is applied to the substrate, the drying temperature is preferably 50° C. or higher and 200° C. or lower. If the temperature is 50° C. or higher, the drying is completed within 3 minutes to 1 hour, which is preferable from the viewpoint of productivity. If the temperature is 200° C. or lower, the cooling time of the substrate after drying is short, which is preferable from the viewpoint of productivity. The temperature for pre-baking the dried substrate is preferably 300° C. to 500° C. If it is 300° C. or higher, the pre-baking can be completed within 3 minutes to 1 hour, which is preferable from the viewpoint of productivity. If it is 500° C. or lower, the cooling time of the dried substrate is shortened, which is preferable from the viewpoint of productivity.

[0027] Coating, drying, and pre-firing are performed to obtain the desired LaNi x My O 3-z This may be repeated to adjust the amount of electrode deposition.

[0028] The firing temperature can be 500°C to 1000°C, but it is preferable to fire at 800°C or higher. When firing at 800°C or higher, LaNi x M y O 3-z It is possible to prepare an electrode having high durability against high-temperature alkali by controlling the XRD main peak position 2θ to be 32.6° or more and 33.2°, which is preferable from the viewpoint of productivity.

[0029] The element M may be added by a method in which a coating liquid containing a water-dispersible sol of a metal salt, or an oxide or hydroxide of La or Ni is applied in advance, dried, and pre-baked, and then a coating liquid containing a water-dispersible sol of a metal salt, oxide, or hydroxide of element M is applied to the electrode in a topcoat manner, dried, pre-baked, and finally baked. Alternatively, the element M may be added by a method in which a coating liquid containing a water-dispersible sol of a metal salt, oxide, or hydroxide of La or Ni is applied in advance, followed by drying, pre-baking, and main baking, and then a coating liquid containing a water-dispersible sol of a metal salt, oxide, or hydroxide of element M is applied to the electrode in a topcoat manner, followed by drying, pre-baking, and main baking.

[0030] (electrolytic cell) FIG. 1 shows a side view of an example of an entire electrolytic cell including an electrolytic cell equipped with the electrode of this embodiment as an anode. FIG. 2 shows a diagram of a zero gap structure of an example of an electrolytic cell including an electrolytic cell equipped with the electrode of this embodiment as an anode (a cross-sectional view of the part enclosed by the dashed square frame shown in FIG. 1). In the bipolar electrolytic cell 50 of this embodiment (see FIG. 3), the diaphragm 4 is in contact with the anode 2a and the cathode 2c to form a zero-gap structure Z (see FIG. 2). An outline of the electrolysis device used in the examples and comparative examples is shown in Fig. 3. Fig. 4 shows an outline of the bipolar electrolysis cell used in the electrolysis tests.

[0031] (element) As shown in FIG. 1, in a bipolar electrolytic cell 50, a bipolar element 60 is disposed between an anode terminal element 51a and a cathode terminal element 51c, and diaphragms 4 are disposed between the anode terminal element 51a and the bipolar element 60, between adjacent bipolar elements 60, and between the bipolar element 60 and the cathode terminal element 51c. In this embodiment, in particular, the portion between the partition walls 1 between two adjacent bipolar elements 60 and the portion between the partition walls 1 between the adjacent bipolar element 60 and the terminal element in the bipolar electrolytic cell 50 are referred to as the electrolytic cell 65. The electrolytic cell 65 includes the partition wall 1, anode chamber 5a, anode 2a, and diaphragm 4 of one element, and the cathode 2c, cathode chamber 5c, and partition wall 1 of the other element.

[0032] (electrode chamber) 2, in the bipolar electrolytic cell 50 of this embodiment, an electrode chamber 5 through which the electrolytic solution passes is defined by the partition wall 1, the outer frame 3, and the diaphragm 4. Here, the electrode chamber 5 on the anode side across the partition wall 1 is the anode chamber 5a, and the electrode chamber 5 on the cathode side is the cathode chamber 5c. In this embodiment, the header pipe of the bipolar electrolytic cell may be of an internal header type or an external header type, and the space occupied by the anode and cathode themselves may be considered to be the space inside the electrode chamber. In particular, when a gas-liquid separation box is provided, the space occupied by the gas-liquid separation box may be considered to be the space inside the electrode chamber.

[0033] (rib) In the bipolar electrolytic cell 65 for alkaline water electrolysis of this embodiment, the rib 6 is preferably physically connected to the electrode 2. With such a configuration, the rib 6 serves as a support for the electrode 2, making it easy to maintain the zero gap structure Z. Furthermore, the rib 6 is preferably electrically connected to the partition wall 1. Furthermore, the provision of the rib 6 can reduce convection that occurs in the electrode chamber 5 due to turbulence in the gas-liquid flow in the electrode chamber 5, thereby suppressing a local increase in the temperature of the electrolyte. Here, an electrode may be provided on the rib, or a current collector, a conductive elastic body, and an electrode may be provided on the rib in this order. In the above-described example of the bipolar electrolytic cell for alkaline water electrolysis, a structure is adopted in which the cathode rib-cathode current collector-conductive elastic body-cathode are stacked in this order in the cathode chamber, and a structure is adopted in which the anode rib-anode are stacked in this order in the anode chamber. In the above-mentioned example of the bipolar electrolytic cell for alkaline water electrolysis, the above-mentioned "cathode rib-cathode current collector-conductive elastic body-cathode" structure is adopted in the cathode chamber, and the above-mentioned "anode rib-anode" structure is adopted in the anode chamber; however, the present invention is not limited to this structure, and an "anode rib-anode current collector-conductive elastic body-anode" structure may also be adopted in the anode chamber. In particular, in the bipolar electrolytic cell for alkaline water electrolysis of the present embodiment, ribs 6 (anode ribs, cathode ribs) are preferably attached to the partition wall 1 as shown in FIG. It is preferable that the ribs (anode ribs, cathode ribs) not only have a role of supporting the anode or cathode but also a role of transmitting current from the partition wall to the anode or cathode. In the bipolar electrolytic cell for alkaline water electrolysis of the present embodiment, it is preferable that at least a part of the rib is conductive, and it is more preferable that the entire rib is conductive. With such a configuration, an increase in cell voltage due to electrode deflection can be suppressed. The material of the rib is generally a conductive metal, such as nickel-plated mild steel, stainless steel, nickel, etc. The material of the rib is preferably the same as that of the partition wall, and most preferably nickel. The distance between adjacent anode ribs or the distance between adjacent cathode ribs is determined taking into consideration the electrolysis pressure and the pressure difference between the anode chamber and the cathode chamber, etc. If the interval between the anode ribs or the interval between the adjacent cathode ribs is too narrow, not only the flow of the electrolyte or gas is hindered, but also the cost is increased. If the rib pitch is 10 mm or more, gas escape to the back surface of the electrode is good. If the rib pitch is too wide, the electrodes (anode and cathode) held by the slight pressure difference between the anode chamber and the cathode chamber are deformed, and the number of anode ribs and cathode ribs is reduced, which increases the electrical resistance. If the rib pitch is 150 mm or less, the electrodes are less likely to bend. The number of ribs, the length of the rib, the angle between the rib and the partition wall, the number of through holes, and the interval (pitch) of the through holes in a given direction along the partition wall may be appropriately determined as long as the effects of the present invention are obtained. The ribs are preferably provided parallel to a given direction along the partition wall (for example, the vertical direction may be set, or the same direction as the direction of one of two pairs of opposing sides when the partition wall has a substantially rectangular shape in plan view as shown in FIG. 3). The rib pitch of the anode rib and the rib pitch of the cathode rib may be the same or different, and it is preferable that the rib pitch of the anode rib and the rib pitch of the cathode rib both satisfy the above range. The anode ribs and cathode ribs are attached to the bulkhead by laser welding or the like. The thickness of the rib may be from 0.5 mm to 5 mm, taking into consideration cost, ease of production, strength, etc., and is not particularly limited to 1 mm to 2 mm. The electrodes and current collectors are usually attached to the ribs by spot welding, but other methods such as laser welding may also be used, or they may be tied together with a wire or string-like member for close contact. The ribs are fixed to the partition wall by spot welding, laser welding, or other means, in the same manner as the anode and cathode.

[0034] (Hydrogen production method) Next, a method for producing hydrogen by alkaline water electrolysis using the bipolar electrolytic cell of this embodiment will be described. In this embodiment, hydrogen is produced at the cathode by applying a current to a bipolar electrolytic cell having an anode and a cathode as described above and circulating an electrolyte, thereby performing water electrolysis. In this case, for example, a variable power supply can be used as the power supply. A variable power supply is a power supply derived from a renewable energy power plant whose output fluctuates in units of a few seconds to a few minutes, unlike a power supply that provides a stable output, such as grid power. The method of generating renewable energy is not particularly limited, but examples include solar power generation and wind power generation. For example, in the case of electrolysis using a bipolar electrolytic cell, the cationic electrolyte in the electrolytic solution moves from the anode chamber of an element through the diaphragm to the cathode chamber of an adjacent element, and the anionic electrolyte moves from the cathode chamber of an element through the diaphragm to the anode chamber of the adjacent element. Thus, the current during electrolysis flows in the direction in which the elements are connected in series. That is, the current flows from the anode chamber of one element to the cathode chamber of the adjacent element through the diaphragm. As a result of electrolysis, oxygen gas is produced in the anode chamber and hydrogen gas is produced in the cathode chamber.

[0035] The bipolar electrolytic cell 65 for alkaline water electrolysis of this embodiment can be used in the bipolar electrolytic cell 50, the electrolytic device 70 for alkaline water electrolysis, etc. An example of the electrolytic device 70 for alkaline water electrolysis includes an apparatus including the bipolar electrolytic cell 50 of this embodiment, a liquid delivery pump 71 for circulating the electrolytic solution, a gas-liquid separation tank 72 for separating the electrolytic solution from hydrogen and / or oxygen, and a water supply device for supplying water consumed by electrolysis. The alkaline water electrolysis apparatus may further include a rectifier 74, an oxygen concentration meter 75, a hydrogen concentration meter 76, a flow meter 77, a pressure meter 78, a heat exchanger 79, a pressure control valve 80, and the like. In the alkaline water electrolysis method using the alkaline water electrolysis apparatus, the current density applied to the electrolysis cell is 4 kA / m 2 ~20kA / m 2 Preferably, 6 kA / m 2 ~15kA / m 2 It is even more preferable that: In particular, when a variable power supply is used, it is preferable to set the upper limit of the current density within the above range.

[0036] The electrodes, electrolytic cells, and hydrogen production methods according to the embodiments of the present invention have been illustrated and described above with reference to the drawings. However, the electrodes, electrolytic cells, and hydrogen production methods according to the present invention are not limited to the above examples, and appropriate modifications can be made to the above embodiments. EXAMPLES

[0037] Example 1 A nickel expand metal with SW 3.0 mm, LW 4.5 mm, thickness 1.2 mm, and aperture ratio 54% was prepared as a nickel porous substrate. After blasting treatment was performed on this nickel expand metal, a substrate with a length of 10 cm and a width of 10 cm was cut out, which was then acid-treated in 6N hydrochloric acid at 50°C for 6 hours, washed with water, and dried to prepare a substrate for coating. Next, solutions A and B were prepared having the composition of Example 1 in Table 1. Solution B was prepared by dissolving ammonium niobium oxalate in pure water, and the Nb concentration was confirmed by ICP-AES (inductively coupled plasma atomic emission spectrometry). Solution A was placed in a rectangular polyethylene container measuring 6 cm x 10 cm and 11 cm in height, and solution B was slowly mixed in while stirring with a magnetic stirrer to prepare the coating solution of Example 1. While stirring the coating liquid, the substrate to be coated was held vertically and the lower half was immersed in the coating liquid, and then the substrate was turned upside down and the upper half was also immersed in the coating liquid. After the coating liquid was applied to the entire surface of the substrate, the substrate was kept vertically oriented and then subjected to an air blowing treatment with an air gun to blow off excess coating liquid. Thereafter, the substrate was dried at 60° C. for 10 minutes and then baked at 400° C. for 10 minutes to form a metal oxide layer on the surface of the substrate. This cycle of coating, drying and firing was repeated 13 times, and then the coating was further fired at 800°C for 1 hour to obtain a coating weight of 40 g / m2 on the coating substrate. 2 A metal oxide layer of the above was formed to obtain an anode for water electrolysis.

[0038] (Examples 2 to 6) A substrate for coating was prepared in the same manner as in Example 1, and liquids A and B having the compositions of Examples 2 to 6 in Table 1 were prepared. Liquids A and B were then mixed in a rectangular polyethylene container in the same manner as in Example 1 to prepare the coating liquids of Examples 2 to 6. After that, a cycle of coating, drying, and baking was repeated in the same manner as in Example 1, and baking was performed at 800°C for 1 hour, resulting in a coating amount of 40 g / m on the substrate for coating. 2 Thus, the water electrolysis anodes of Examples 2 to 6 were obtained.

[0039] Example 7 9.30 g of Ni(NO3)2·6H2O, 34.64 g of La(NO3)3·6H2O, 30.03 g of glycine (C2H5NO2), and 13.78 g of Mn(NO3)2·6H2O were dissolved in 400 g of pure water to prepare the coating solution of Example 7. This coating solution was then transferred to a polyethylene container with a base of 13 cm × 13 cm and a height of 10 cm. A substrate for coating was prepared in the same manner as in Example 1. This substrate was completely immersed in the coating liquid in a container and then pulled out, the coating liquid was applied to the entire surface of the substrate, and the substrate was then turned vertically and the excess coating liquid was blown off by air blowing treatment using an air gun. Thereafter, the substrate was dried at 60° C. for 10 minutes and then baked at 400° C. for 10 minutes to form a metal oxide layer on the surface of the substrate. This cycle of coating, drying and firing was repeated 13 times, and then the coating was further fired at 800°C for 1 hour to obtain a coating weight of 40 g / m2 on the coating substrate. 2 A metal oxide layer of the above was formed to obtain an anode for water electrolysis.

[0040] Example 8 18.61 g of Ni(NO3)2·6H2O, 34.64 g of La(NO3)3·6H2O, and 27.63 g of glycine were dissolved in 200 g of pure water to prepare Solution A of Example 8. Pure water was added to TiO2 sol with a primary particle size of 10 nm to dilute it, preparing a TiO2 sol with a Ti concentration of 80 mmol / kg sol, which was used as Solution B of Example 8. As in Example 1, liquid A and liquid B were mixed in a rectangular polyethylene container to prepare a coating liquid for Example 8. After repeating the cycle of coating, drying and baking in the same manner as in Example 1, baking was performed at 800°C for 1 hour to obtain a coating liquid with a deposition amount of 40 g / m2 on the coating substrate.2 Thus, a water electrolysis anode of Example 8 was obtained.

[0041] Example 9 The coating solution of Example 7 was prepared by dissolving 20.93 g of Ni(NO3)2·6H2O, 34.64 g of La(NO3)3·6H2O, 30.03 g of glycine, and 2.14 g of ZrO(NO3)2·2H2O in 400 g of pure water. Thereafter, the same procedure as in Example 7 was carried out to obtain an anode for water electrolysis of Example 9.

[0042] Example 10 The coating solution of Example 10 was prepared by dissolving 26.75 g of Ni(NO3)2·6H2O, 34.64 g of La(NO3)3·6H2O, 31.83 g of glycine, and 1.43 g of TaCl5 in 400 g of pure water. Thereafter, in the same manner as in Example 7, an anode for water electrolysis of Example 10 was obtained.

[0043] Example 11 17.45 g of Ni(NO3)2·6H2O, 34.64 g of La(NO3)3·6H2O, and 27.03 g of glycine were dissolved in 200 g of pure water to prepare Solution A of Example 11. Antimony tartrate was dissolved in pure water to prepare an antimony tartrate solution with an Sb concentration of 20 mmol / kg, which was used as Solution B of Example 11. The Sb concentration was confirmed by ICP-AES (inductively coupled plasma atomic emission spectroscopy). Liquid A and Liquid B were mixed in a rectangular polyethylene container in the same manner as in Example 1 to prepare a coating liquid for Example 11. After repeating a cycle of coating, drying and baking in the same manner as in Example 1, the liquid was baked at 800°C for 1 hour to obtain a coating liquid with a deposition amount of 40 g / m2 on the substrate for coating. 2 A metal oxide layer of the above was formed to obtain an anode for water electrolysis of Example 11.

[0044] Example 12 A coating solution of Example 12 was prepared by dissolving 23.26 g of Ni(NO3)2·6H2O, 34.64 g of La(NO3)3·6H2O, and 30.03 g of glycine in 400 g of pure water. A substrate for application was prepared in the same manner as in Example 1, and the coating liquid was applied to both sides of the substrate using a spray coating device (rCoater sold by Asahi Sunac Corporation). The substrate was then dried at 60°C for 10 minutes and then baked at 400°C for 10 minutes to form a metal oxide layer on the substrate surface. This cycle of coating, drying and baking was repeated 24 times. Furthermore, Nb2O5 sol with a primary particle size of 5 nm or less was diluted to prepare Nb2O5 sol with an Nb concentration of 200 mmol / kg sol. This Nb2O5 sol was applied to both sides using a spray coater, then dried at 60℃ for 10 minutes, and the weight increase was calculated to be 38mg compared to the substrate before application. Since the amount of LaNiO3 supported on the substrate was 1.4g, the weight of 1 mole of LaNiO3 was 245.6g, and the weight of 1 mole of Nb2O5 was 265.2g, it was found that by applying 38mg of Nb2O5, the ratio of Nb applied to 1 mole of LaNiO3 was 0.05 moles. The substrate was dried at 60℃ for 10 minutes, baked at 400℃ for 10 minutes, and then baked at 800℃ for 1 hour, resulting in a coating weight of 144g / m 2 A metal oxide layer of the above was formed to obtain an anode for water electrolysis of Example 12.

[0045] Example 13 The coating solution of Example 13 was prepared in the same manner as in Example 12. Thereafter, this coating solution was transferred to a polyethylene container having a base of 13 cm×13 cm and a height of 10 cm. A substrate for coating was prepared in the same manner as in Example 1. This substrate was completely immersed in the coating solution in the container and then pulled out. After the coating solution was applied to the entire surface of the substrate, the substrate was turned sideways and the excess coating solution was blown off by air blowing with an air gun. Then, the substrate was dried at 60°C for 10 minutes and further baked at 400°C for 10 minutes to form a metal oxide layer on the substrate surface. This cycle of coating, drying and baking was repeated 24 times. Ammonium niobium oxalate was dissolved in pure water to prepare an aqueous solution of ammonium niobium oxalate with a Nb concentration of 43.8 mmol / kg. This aqueous solution of ammonium niobium oxalate was transferred to a polyethylene container with a base of 13 cm x 13 cm and a height of 10 cm. The substrate with a metal oxide layer formed on its surface was completely immersed in an aqueous solution of ammonium niobium oxalate and pulled out. After the coating solution was applied to the entire surface of the substrate, the substrate was turned sideways and a weak breeze was applied from an air gun to remove the coating solution that had clogged the substrate. When the weight of the substrate was measured after the air gun treatment, it was found that 1.3 g of the aqueous solution of ammonium niobium oxalate had been applied to the substrate. Since the amount of LaNiO3 supported on the substrate was 1.4 g and the weight of 1 mole of LaNiO3 was 245.6 g, it was found that by applying 1.3 g of the aqueous solution of ammonium niobium oxalate with an Nb concentration of 43.8 mmol / kg, Nb was applied at a ratio of 0.01 mole to 1 mole of LaNiO3. The substrate coated with the aqueous solution of ammonium niobium oxalate was dried at 60°C for 10 minutes, then baked at 400°C for 10 minutes and further baked at 800°C for 1 hour, resulting in a coating weight of 141 g / m 2 A metal oxide layer of the above was formed to obtain an anode for water electrolysis of Example 13.

[0046] Example 14 In the same manner as in Example 13, the cycle of drying and firing was repeated 24 times, and then firing was carried out at 800° C. for 1 hour to form a metal oxide layer on the surface of the substrate. Ammonium niobium oxalate was dissolved in pure water to prepare an aqueous solution of ammonium niobium oxalate with a Nb concentration of 87.7 mmol / kg. This aqueous solution of ammonium niobium oxalate was transferred to a polyethylene container with a base of 13 cm x 13 cm and a height of 10 cm. The substrate with a metal oxide layer formed on its surface was completely immersed in an aqueous solution of ammonium niobium oxalate and pulled out. After the coating solution was applied to the entire surface of the substrate, the substrate was turned sideways and a weak breeze was applied from an air gun to remove the coating solution that had clogged the substrate. When the weight of the substrate was measured after the air gun treatment, it was found that 1.3 g of the aqueous solution of ammonium niobium oxalate had been applied to the substrate. Since the amount of LaNiO3 supported on the substrate was 1.4 g and the weight of 1 mole of LaNiO3 was 245.6 g, it was found that by applying 1.3 g of the aqueous solution of ammonium niobium oxalate with an Nb concentration of 87.7 mmol / kg, 0.02 moles of Nb were applied to 1 mole of LaNiO3. The substrate coated with the aqueous solution of ammonium niobium oxalate was dried at 60°C for 10 minutes, then baked at 400°C for 10 minutes and further baked at 800°C for 1 hour, resulting in a coating weight of 142 g / m 2 A metal oxide layer of the above was formed to obtain an anode for water electrolysis of Example 14.

[0047] Example 15 In the same manner as in Example 13, the cycle of drying and firing was repeated 33 times, and then firing was carried out at 800° C. for 1 hour to form a metal oxide layer on the surface of the substrate. Then, an aqueous solution of ammonium niobium oxalate with a Nb concentration of 125 mmol / kg was prepared, and in the same manner as in Example 14, Nb was applied at a ratio of 0.02 moles per mole of LaNiO3, dried at 60°C for 10 minutes, baked at 400°C for 10 minutes, and further baked at 800°C for 1 hour, resulting in a coating weight of 202 g / m 2 A metal oxide layer of the above was formed to obtain an anode for water electrolysis of Example 15.

[0048] Comparative Example 1 A substrate for application was prepared in the same manner as in Example 1. Next, a coating solution was prepared by mixing lanthanum acetate 1.5-hydrate and nickel nitrate hexahydrate to have concentrations of 0.20 mol / L and 0.20 mol / L, respectively. A vat containing the above coating liquid was placed at the bottom of the coating roll, the coating liquid was soaked into an EPDM coating roll, a roll was placed above it so that the roll and the coating liquid were always in contact, and a PVC roller was placed on top of that to apply the coating liquid to the substrate (roll method). The substrate was quickly passed between two EPDM sponge rolls before the coating liquid dried. After that, it was dried at 50°C for 10 minutes, and then baked at 400°C for 10 minutes in a muffle furnace to form a metal oxide layer on the substrate surface. This cycle of roll coating, drying and firing was repeated 13 times, and then the coating was further fired at 800°C for 1 hour, resulting in a coating weight of 42 g / m 2 A metal oxide layer of the above was formed to obtain an anode for water electrolysis.

[0049] Comparative Example 2 A substrate for application was prepared in the same manner as in Example 1. Next, coating solutions were prepared so that lanthanum nitrate hexahydrate, nickel nitrate hexahydrate, ammonium niobium oxalate n-hydrate, and glycine had concentrations of 0.20 mol / L, 0.16 mol / L, 0.04 mol / L, and 0.36 mol / L, respectively. As in Comparative Example 1, the cycle of roll coating, drying and firing was repeated 40 times by the roll method, and then firing was further carried out at 700°C for 1 hour to form a metal oxide layer, with a coating weight of 145 g / m 2 Thus, an anode for water electrolysis was obtained.

[0050] (XRD measurement method) The test anode was cut to 2 cm x 2 cm and measured using an XRD measurement device D8 ADVANCE (sold by Bruker Japan Co., Ltd.). The test anode was placed at the center of a bulk sample holder (groove φ40 mm, depth 6 mm, material PMMA), and pieces of clay were placed under the four corners of the sample electrode so that the surface height was the same as the height of the edge of the holder, and the sample electrode was pressed down and fixed from above. The measurement was performed by rotating the sample at 15 rpm, dividing the range of 2θ = 10 ° to 70 ° into 3080 steps, and measuring one step for 4 seconds. X-rays were used, and the voltage of the X-ray source was 40 kV and the current was 40 mA. A divergence slit of 0.8 ° was used. Table 2 shows the settings (overview data) of the device, such as the detector and filter, which can be confirmed with the measurement condition setting software XRD WIZARD. Using the analysis software DIFFRAC.EVA, a peak search was performed on the XRD spectrum using the "peak search" tool, and the 2θ of the peak position of each peak was determined. LaNi x M y O 3-z The main peak position of was calculated by detecting the NiO main peak near 2θ = 43.276° by peak search, and then shift-correcting the XRD spectrum using the "X-axis offset" tool so that the detected value of the NiO main peak position 2θ was 2θ = 43.276° for the (200) plane of the NiO PDF00-047-1049 card data. LaNix M y O 3-z The main peak position of LaNi shifts depending on the sample, but the peak position around 2θ=32.5°~33.2° is selected based on the (104) plane main peak position 2θ=33.166° on the PDF01-070-5757 card. x M y O 3-z The main peak position was determined as LaNi x M y O 3-z The main peak intensity of LaNi was calculated using the "Peak Search" tool. x M y O 3-z The net intensity of the main peak was used. LaNi x M y O 3-z The main peak half-width was determined by using the "Create Area" tool in the analysis software DIFFRAC.EVA to select an area by setting the left end at 31° and the right end at 35°, and then calculating the half-width.

[0051] (Alkaline resistance test) The test anode was cut into a size of 2 cm x 2 cm, and XRD was measured. x M y O 3-z The main peak intensity was calculated. The alkali resistance test was carried out according to the following procedure. The test anode was placed in a 19 mL PFA sealed container (outer diameter 30 mmφ, height including lid 44 mm, capacity), and the container was filled with an 8 mol / L potassium hydroxide aqueous solution (sold by Kanto Chemical Co., Ltd.) and sealed. The PFA sealed container was then placed in a constant temperature incubator (product name DKN402, manufactured by Yamato Scientific Co., Ltd.) and heated so that the temperature of the liquid in the sealed container reached 90°C. The liquid temperature was maintained at 90°C for 24 hours, after which the sealed container was removed from the constant temperature incubator and cooled on ice. The electrode was removed from the sealed container, washed with water, dried, and then the XRD was measured again. x M y O 3-z The main peak intensity was calculated. As an index of alkali resistance, the peak strength retention rate was calculated by the following formula. (Peak strength retention rate (%)) = (LaNi after alkali resistance test x M y O 3-z XRD main peak intensity) / (LaNi before alkali resistance test x M y O 3-z (XRD main peak intensity) × 100 The evaluation results for Examples 1 to 15 and Comparative Examples 1 and 2 are shown in Table 3.

[0052] (Measurement of oxygen overvoltage after alkaline resistance test of anode) The oxygen overvoltage of the anode after the alkali resistance test was measured by the following procedure. After the alkali resistance test, the anode (2 cm x 2 cm) was fixed to a PTFE-coated nickel rod with a nickel screw. A platinum mesh was used as the counter electrode, and the anode was subjected to a current density of 6 kA / m in a 32 wt% sodium hydroxide aqueous solution at 80°C. 2 The electrolyte was electrolyzed with 0.1% NaCl and the oxygen overvoltage was measured. The oxygen overvoltage was measured by the three-electrode method using a Luggin capillary in order to eliminate the effect of ohmic loss due to the electrolyte resistance. The distance between the tip of the Luggin capillary and the anode was always fixed at 1 mm. The device used to measure the oxygen overvoltage was a Solartron potentiogalvanostat "1470E System." Silver-silver chloride (Ag / AgCl) was used as the reference electrode for the three-electrode method. The electrolyte resistance that could not be completely eliminated by the three-electrode method was measured by the AC impedance method, and the oxygen overvoltage was corrected based on the measured electrolyte resistance. A Solartron frequency response analyzer “1255B” was used to obtain a Cole-Cole plot of the real and imaginary parts, and the electrolyte resistance and double layer capacitance were calculated by analyzing the plot using equivalent circuit fitting. The ohmic loss that could not be completely eliminated by the three-electrode method was measured by the AC impedance method, and the oxygen overvoltage was corrected based on the measured ohmic loss. The frequency characteristic analyzer "1255B" manufactured by Solartron was used to measure the ohmic loss. The evaluation results for Examples 1 to 15 and Comparative Examples 1 and 2 are shown in Table 3.

[0053] (Example 16) An electrolytic cell for alkaline water electrolysis and a bipolar electrolytic cell were prepared as follows. -anode- It was prepared in the same manner as in Example 14. -cathode- The conductive substrate used was a plain weave mesh substrate made of nickel thin wires with a diameter of 0.15 mm woven at 40 meshes, on which platinum was supported. -Partition walls, outer frames- The bipolar element used had a partition wall separating the anode and cathode and an outer frame surrounding the partition wall. All of the materials of the members that come into contact with the electrolyte, such as the partition wall and the frame of the bipolar element, were made of nickel. -Conductive elastic body- The conductive elastic body used was made by weaving nickel wire with a wire diameter of 0.15 mm and corrugating it to a wave height of 5 mm. -diaphragm- A coating solution having the following component composition was obtained using zirconium oxide (product name "EP Zirconium Oxide", manufactured by Daiichi Kigenso Kagaku Kogyo Co., Ltd.), N-methyl-2-pyrrolidone (manufactured by Wako Pure Chemical Industries, Ltd.), polysulfone ("Udel" (registered trademark), manufactured by Solvay Advanced Polymers), and polyvinylpyrrolidone (weight average molecular weight (Mw) 900,000, manufactured by Wako Pure Chemical Industries, Ltd.). Polysulfone: 15 parts by weight Polyvinylpyrrolidone: 6 parts by weight N-methyl-2-pyrrolidone: 70 parts by weight Zirconium oxide: 45 parts by mass The above coating liquid was applied to both surfaces of a substrate, a polyphenylene sulfide mesh (manufactured by Kureha Co., Ltd., film thickness 280 μm, mesh size 358 μm, fiber diameter 150 μm). Immediately after coating, the substrate coated with the coating liquid was exposed to steam, and then immersed in a coagulation bath to form a coating film on the substrate surface. The coating film was then thoroughly washed with pure water to obtain a porous film. -gasket- The gasket used was a square with an inner dimension of 504 mm square, 4.0 mm thick and 18 mm wide, with an opening on the inside that was the same dimensions as the electrode chamber in a plan view, and a slit structure for inserting and holding the diaphragm. -Zero gap type multi-pole element- The external header type zero gap cell unit 60 is a rectangle of 540 mm x 620 mm, and the area of ​​the current-carrying surface of the anode 2a and cathode 2c is 500 mm x 500 mm. The cathode side of the zero gap type bipolar element 60 has a cathode chamber 5c in which the cathode 2c, conductive elastomer 2e, and cathode current collector 2r are laminated and connected to the partition wall 1 via the cathode rib 6, and an electrolyte flows. The anode side has an anode chamber 5a in which the anode 2a is connected to the partition wall 1 via the anode rib 6, and an electrolyte flows (Fig. 2). The depth of the anode chamber 5a (anode chamber depth, the distance between the partition wall and the anode in FIG. 2) was 25 mm, and the depth of the cathode chamber 5c (cathode chamber depth, the distance between the partition wall and the cathode current collector in FIG. 2) was 25 mm, and the material was nickel. The thickness of the nickel partition wall 1 to which the nickel anode rib 6 with a height of 25 mm and a thickness of 1.5 mm and the nickel cathode rib 6 with a height of 25 mm and a thickness of 1.5 mm were attached by welding was 2 mm. A nickel expand base material that had been blasted in advance was used as the cathode current collector 2r. The base material had a thickness of 1 mm and an aperture ratio of 54%. The conductive elastic body 2e was fixed onto the cathode current collector 2r by spot welding. By stacking this zero-gap type bipolar element via a gasket that holds the diaphragm, a zero-gap structure Z in which the anode 2a and the cathode 2c are pressed against the diaphragm 4 can be formed.

[0054] Comparative Example 3 Except for using an anode prepared in the same manner as in Comparative Example 2, 16 A zero-gap type bipolar element was manufactured in the same manner as described above.

[0055] Using the electrolysis devices of Example 16 and Comparative Example 3, the electrolyte was kept at 90°C and circulated for 24 hours, after which the electrolyte temperature was lowered to 80°C and the current density was increased to 6 kA / m 2Water electrolysis was performed by continuously applying positive current for 500 hours so that the voltage of each cell in Example 16 and Comparative Example 3 was monitored, and the change in the voltage of each cell was recorded. The cell voltage of each cell was compared by taking the average value of three cells in each of Example 16 and Comparative Example 3. In Example 16, 3 cells Average Voltage However, after 500 hours of current application, the voltage was a low 1.77V, whereas in Comparative Example 3, the voltage was 1.77V for the three cells. Average Voltage However, after 500 hours of current application, a high value of 1.95 V was obtained. Therefore, it can be concluded that the anode of Example 16 has higher alkali durability than Comparative Example 3, and thus a low cell voltage can be achieved even during long-term operation.

[0056] [Table 1]

[0057] [Table 2]

[0058] [Table 3] [Industrial Applicability]

[0059] INDUSTRIAL APPLICABILITY The electrode of the present invention has a low overvoltage for oxygen generation and is highly durable against high-temperature alkali, and therefore can be suitably used as an anode of a water electrolysis cell in the electrolysis of water containing alkali. [Explanation of symbols]

[0060] 1 Bulkhead 2 electrodes 2a anode 2c cathode 2e Conductive elastic body 2r Cathode current collector 3 Outer frame 4 Diaphragm 5a Anode chamber 5c cathode chamber 6. Ribs 7 Gasket 50 bipolar electrolyzer 51g fast head, loose head 51i Insulating plate 51a Anode terminal element 51c Cathode Terminal Element 51r tie rod 60 Multi-pole element 65 Electrolysis Cell 70 Electrolyzer 71 Liquid delivery pump 72 Gas-liquid separation tank 74 Rectifier 75 Oxygen concentration meter 76 Hydrogen concentration meter 77 Flow meter 78 Pressure Gauge 79 Heat exchanger 80 Pressure Control Valve Z Zero gap structure

Claims

1. On the substrate, LaNi x M y O 3-z (x+y is 0.8 or more and 1.2 or less, y is 0.001 or more and 0.15 or less, z is -0.5 or more and 0.5 or less, and M contains at least one of Nb and Sb), x M y O 3-z The electrode is characterized in that the XRD main peak position 2θ is 32.6° or more and 33.2° or less.

2. The electrode according to claim 1 , wherein y is equal to or greater than 0.002 and less than 0.

2.

3. The LaNi x M y O 3-z 3. The electrode according to claim 1 or 2, wherein the XRD main peak position 2θ is 32.7° or more and 33.2° or less.

4. The electrode according to any one of claims 1 to 3, wherein M is Nb.

5. The LaNi x M y O 3-z The electrode according to any one of claims 1 to 4, wherein the XRD main peak half width is 0.6° or more and 0.85° or less.

6. The LaNi x M y O 3-z The electrode according to any one of claims 1 to 5, wherein the XRD main peak intensity is 6,000 or more and 100,000 or less.

7. 7. An electrolytic cell comprising the electrode according to claim 1 as an anode.

8. In a method for producing hydrogen by electrolyzing water containing an alkali in an electrolytic cell, the electrolytic cell is provided with at least an anode and a cathode, and the anode is provided with a LaNi x M y O 3-z (x+y is 0.8 or more and 1.2 or less, y is 0.001 or more and 0.15 or less, z is -0.5 or more and 0.5 or less, and M contains at least one of Nb and Sb), x M y O 3-z The method for producing hydrogen is characterized in that the XRD main peak position 2θ is 32.6° or more and 33.2° or less.

Citation Information

Patent Citations

  • Piezoelectric thin film element, piezoelectric thin film device, and method of manufacturing the piezoelectric thin film element

    JP2011035370A

  • Anode for alkali water electrolysis and manufacturing method of anode for alkali water electrolysis

    JP2017190476A

  • Method for evaluating electrode for alkaline water electrolysis, method for manufacturing electrode for alkaline water electrolysis, and electrode for alkaline water electrolysis

    JP2019143235A

  • Electrochemical Methods and Systems Using Catalytic Materials

    US20130020207A1

  • Positive electrode, positive electrode for water electrolysis, electrolysis cell, and method for producing hydrogen

    WO2018155503A1